Jamaica. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The Inter-American Institute for Cooperation on Agriculture (IICA) led several significant projects in Jamaica in 2023. One of these was a rapid soil health assessment to address declining cocoa and coffee productivity. This assessment, funded by the International Trade Centre, revealed that soil health on coffee and cocoa farms was suboptimal, leading to recommendations to improve productivity, such as the use of compost and the application of special fertilizers. Also of note was an online course on Rural Tourism for the Caribbean, with more than 300 participants successfully completing the program. This course, presented by IICA, explored rural tourism options and opportunities, receiving high marks from the participants. Another important project focused on the management of cadmium levels in cocoa in Latin America and the Caribbean. An important milestone was reached with the signing of agreements between IICA and the National Project Executing Agencies in several countries, laying the groundwork for the implementation of activities to mitigate cadmium levels in the cocoa value chain. Progress was also made in the biofortification of rice in Guyana, with the launch of a rice variety biofortified with zinc, and in Belize, bean varieties with a significantly higher mineral content were identified. Finally, assessments were made of post-harvest facilities and the potential of the millet crop for animal feed, as well as activities to strengthen the food security system and participation in international meetings on food security and agricultural health. These projects reflect IICA's efforts to improve agricultural productivity, strengthen food security and promote sustainable practices in Jamaica.